تقويم أداء مدرّسي مرحلة التعليم الثانوي في ضوء معايير إدارة الجودة الشاملة دراسة ميدانية لاستقصاء آراء المديرين والموجهين التربويين في مدينة اللاذقية - طيوب, محمود; درويش, رمضان; حسين, محمود حسن (مجلة جامعة تشرين للبحوث والدراسات العلمية- سلسلة العلوم الاقتصادية والقانونية, 2013)
يتناول البحث تقويم أداء مدرّسي مرحلة التعليم الثانوي في مدينة اللاذقية وفق معايير إدارة الجودة الشاملة من وجهة نظر الموجهين التربويين ومديري المدارس في المجالات التالية: تخطيط وتصميم المواقف التعليمية, إدارة الصف والعلاقة مع الطلاب, التمكن من المادة التعليمية ومتابعتها, استخدام التقنيات الحديثة, تقويم الطلاب, العلاقة مع المجتمع المحلي. ولتحقيق أهداف البحث تمّ تصميم استبانة مؤلفة من (37) بنداً تغطي مجالات البحث, وتوزيعها على عينة من (41) موجهاً تربوياً, و(23) مدير مدرسة ثانوية في مدينة اللاذقية, وبعد الدراسة والتحليل تمّ التوصل إلى النتائج التالية: يتوافق أداء مدرّسي مرحلة التعليم الثانوي في مجالات:(تخطيط وتصميم المواقف التعليمية, إدارة الصف والعلاقة مع الطلاب, التمكن من المادة العلمية ومتابعتها, تقويم الطلاب, العلاقة مع المجتمع المحلي), بشكل كبير مع معايير إدارة الجودة الشاملة. يتوافق أداء مدرّسي مرحلة التعليم الثانوي في مجال استخدام التقنيات الحديثة بشكل محدود مع معايير إدارة الجودة الشاملة. عدم وجود فروق ذات دلالة إحصائية بين متوسطات تقديرات الموجهين التربويين ومديري المدارس في مستوى أداء مدرّسي مرحلة التعليم الثانوي فيما يتعلق بالمجالات المدروسة, وهذا يدل على التوافق بين الموجهين التربويين ومديري المدارس على مستوى الأداء الفعلي لمدرّسي مرحلة التعليم الثانوي في ضوء معايير إدارة الجودة الشاملة. وكان من أهم توصيات البحث: يجب على المدرّسين الاهتمام بالتحسين المستمر والتطوير الدائم للأداء من خلال المشاركة في أنشطة التنمية المهنية المناسبة لهم, لضمان تحقيق الجودة والتميز عند أدائهم لمهنة التدريس. يجب على المدرّسين استخدام التجهيزات والتقنيات الحديثة المتاحة, وتطبيق الاستراتيجيات التدريسية الحديثة كالتعليم التعاوني والتعليم عن بعد والتعليم باستخدام الحاسوب. The research handles the evaluation of the performance of teachers of secondary education in the city of Latakia according to the criteria of total quality management from the perspective of supervisors and school directors in the following areas: planning and design of educational situations, classroom management and the relationship with the students, mastery of educational material and follow-up, use of modern techniques, student assessment, and the relationship with the local community. To achieve the objectives of the research, a questionnaire was designed consisting of (37) items covering the fields of research, and distributed to a sample of (41) educational supervisors, and (23) High School directors in the city of Lattakia. The study and analysis came up with following results: 1- The performance of the secondary school teachers is consistent in the areas of: (planning and design of educational situations, classroom management and the relationship with the students, mastery of the scientific material and its follow-up, student assessment, the relationship with the local community), significantly with total quality management standards. 2- The performance of secondary school teachers is consistent in the use of modern technologies in a limited way with total quality management standards. 3- There are no statistically significant differences between the average estimates of supervisors and school administrators in the level of performance of teachers of secondary education regarding the areas under study, and this shows consistency between supervisors and school administrators at the level of the actual performance of teachers of secondary education in the light of the criteria of Total Quality Management. The most important recommendations: 1- Teachers must pay attention to continuous improvement and constant development of performance through participation in professional development activities suitable for them, to ensure quality and distinction in the performance of the teaching profession. 2- Teachers must use modern equipment and techniques available, and apply modern teaching strategies such as cooperative education, distance education and computer-based education.